Implementasi Metode Drill dan Hafalan pada Program Kilatan 40 Hari dalam Menguatkan Pemahaman Santri terhadap Nahwu dan Sharaf Pondok Pesantren Al-Hasani Logawe Tuban - Mochammad Zakaria; Yogi Prana Izza; Saeful Anwar; Ahmad Muthi'uddin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This paper discusses the importance of mastering nahwu and sharaf (Arabic grammar) in pesantren (Islamic boarding schools) as a fundamental foundation for understanding classical Arabic texts, particularly the kitab kuning. The study focuses on the implementation of drill and memorization methods in the intensive 40-day Kilatan program at Pondok Pesantren Al-Hasani Logawe. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The drill method involved daily repetition, interactive questioning, and direct application of grammatical rules. Memorization was conducted independently and submitted before new material was introduced. The program was carried out continuously for 40 days without breaks, following a structured and consistent schedule. Supporting factors included well-organized material, disciplined scheduling, a conducive learning environment, and high student enthusiasm. Challenges faced during implementation included low motivation among some students and limited study time. However, the institution addressed these through additional review sessions and opportunities to participate in subsequent program batches. Results indicate that the applied methods effectively enhanced students’ understanding and mastery of nahwu and sharaf.